Prolonged dormancy interacts with senescence for two perennial herbs. (24th April 2013) - Tuomi, Juha; Crone, Elizabeth E.; Gremer, Jennifer R.; Jäkäläniemi, Anne; Lesica, Peter; Pedersen, Bård; Ramula, Satu
Summary: Senescence is characterized by a decline in survival, fecundity and reproductive value with age among adult individuals. Simple age‐dependent life cycles progress forward through developmental stages, with each successive stage being characterized by age‐specific vital rates. In contrast, size‐ or stage‐based life cycles for perennial plants are more complex and often include stasis and retrogression to previous vegetative or reproductive life stages, indicating possible slowing or even reversing the developmental progress. Many plants remain in nonemergent, below‐ground stages during the growing season (prolonged dormancy), which may affect the process of senescence. Stasis in the dormant stage implies that senescence is interrupted while plants are below‐ground. We explored the underlying assumptions of size‐ or stage‐based life cycle graphs and developed four different demographic models for how prolonged dormancy may mediate the relationship between age and vital rates. We then tested these models using more than 20 years of demographic data on 2 perennial herbs, Astragalus scaphoides and Silene spaldingii . Results from model fitting suggest that prolonged dormancy interacts with the age dependence of vital rates. The model using true biological age (time since germination) of emergent and dormant plants to estimate vital rates was never the best model for our data. For both species, the model assuming that dormancy resets plants to the same postdormant state experienced earlier in life independent of their predormant age resulted in the best fit, though not for every vital rate. Older Astragalus plants had declining annual survival probabilities and reproductive value, suggesting senescence. Silene showed the opposite pattern for reproductive value that increased with age, indicating negative senescence. Synthesis . Using long‐term demographic data from two perennial herbs, this study shows mixed evidence for senescence in perennial plants. Our results indicate that prolonged dormancy interacts with the age dependence of vital rates and may sometimes retard the process of senescence. Abstract : We develop a modelling framework for how prolonged dormancy may affect senescence in perennial plants. Using this framework for long‐term demographic data from two perennial herbs, the present study shows mixed evidence for senescence in perennial plants. Our results indicate that prolonged dormancy interacts with the age‐dependence of vital rates and may sometimes retard the process of senescence.